Phát triển năng lực giải quyết vấn đề của học sinh trong hoạt động giải bài tập động lực học lớp 10 trường PTTH - Nguyễn, Thế Khôi (Bộ Giáo dục và Đào tạo, 2013)
This article mainly deals with following contents: The relation between physical excercises and developing the ahility for solving problems of pupils; The standards of developing that ability for doing tenth form dynamics exceeises in secodary schooI.